If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12n + 4p = 0 Solving 12n + 4p = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4p' to each side of the equation. 12n + 4p + -4p = 0 + -4p Combine like terms: 4p + -4p = 0 12n + 0 = 0 + -4p 12n = 0 + -4p Remove the zero: 12n = -4p Divide each side by '12'. n = -0.3333333333p Simplifying n = -0.3333333333p
| Y=x^2-14+24 | | 3c^2+3c-1=0 | | 7x-17+8x-13=180 | | 8x+13=-3x-19 | | 7x-21=2x+3(5x+3) | | -2(5x+2x)+-14x= | | 2x-11-(3x+1)=5x-(4x+2) | | 2(1+6x)=14 | | cos(x-30)=0 | | M+10x=180 | | 20m+15k= | | x-9/3 | | x-/3 | | 5x-20+110=180 | | 4(26)+4=5x-22 | | x^2+3x-1=12 | | F(x)=9x+2mx+m | | 4(4+7x)=14 | | 8-2(-5)=x-3 | | 5(n-1)=-25 | | lnt=.05 | | -4w+16=-8(w-1) | | -2/x=0 | | 2x(-60)=-22 | | 21-n=11 | | -4(3-y)+3y=3(y-4) | | x+2*-1=4 | | 6+6x+5x=39 | | 7x-1=3(-2)-9 | | 7(y+12)=0 | | 6+6x+5x=38 | | 7.25*4+2x=32 |